Fracture-resistant white transparent ABS (acrylonitrile butadiene styrene) resin and preparation method thereof

By introducing acrylic monomers in the preparation process of transparent ABS resin, the refractive index and glass transition temperature of the resin are regulated, and the problem of insufficient anti-blade performance of existing transparent ABS resin is solved, and better anti-blade performance and stress whitening suppression effect are achieved.

CN119735908APending Publication Date: 2025-04-01TIANJIN DAGU CHEM CO LTD

Patent Information

Application Number
CN202411849410.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing transparent ABS resin has insufficient anti-blade performance during application, resulting in stress whitening, affecting its application in packaging and medical fields.

Method used

By introducing acrylic monomers with a low refractive index and glass transition temperature during the copolymerization of styrene and butadiene, the refractive index and glass transition temperature of the resin are regulated, stress whitening phenomenon is suppressed, and an anti-broken white transparent ABS resin is prepared.

Benefits of technology

It significantly improves the anti-blade performance of transparent ABS resin, reduces the occurrence of stress whitening, and meets application needs in packaging and medical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735908A_ABST
    Figure CN119735908A_ABST
Patent Text Reader

Abstract

The invention discloses anti-bending white transparent ABS resin and a preparation method thereof, and belongs to the technical field of synthetic resin. According to the preparation method, styrene and butadiene are copolymerized, so that the refractive index (1.51-1.56) and the glass-transition temperature (-100 to-25 DEG C) of a rubber phase are improved, and then an acrylic monomer with relatively low refractive index and glass-transition temperature is introduced as a functional monomer to regulate and control the refractive index and the glass-transition temperature in the grafting and body MSAN resin preparation process; further, the stress whitening phenomenon is inhibited, and the anti-bending white transparent ABS resin is prepared. According to the embodiment, the impact strength of the prepared transparent ABS resin is larger than 100 J / m, the light transmittance is larger than 88%, the haze is smaller than 6, the daily use requirement is met, the diameter of a stress whitening area is smaller than 3 mm, the transparent ABS resin has obvious anti-folding and anti-whitening performance, and the anti-folding and anti-whitening performance of the transparent ABS resin prepared from the rubber particles with the small particle size is superior to that of similar products with the large particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthetic resins, and in particular relates to a fold-resistant white transparent ABS resin (MABS resin) and a preparation method thereof. Background Art

[0002] ABS resin is a terpolymer composed of acrylonitrile, butadiene and styrene. Its structure is a typical sea-island structure, with the resin phase as the continuous phase and the rubber phase as the dispersed phase. General ABS resin is opaque and white or light yellow. Transparent ABS resin is made by introducing the fourth monomer methyl methacrylate (MMA) into its composition. The content of MMA is used to regulate the refractive index of the resin phase and the rubber phase to make their refractive index similar, thereby reducing the refraction and scattering of light, thereby achieving the transparency of ABS resin. Therefore, transparent ABS resin is also called MABS resin.

[0003] From the perspective of technology, the preparation methods of transparent ABS resin can be divided into two types, namely, bulk method and emulsion bulk blending method, both of which have industrial products in the industry. The emulsion grafting-bulk SAN blending method is to prepare polybutadiene or styrene butadiene emulsion by emulsion polymerization technology, and then use this emulsion as the core layer emulsion, and use emulsion grafting polymerization technology to graft copolymers of styrene, acrylonitrile and methyl methacrylate on its surface to form MABS graft copolymer emulsion. After flocculation and demulsification, MABS high rubber powder can be obtained; after preparing MSAN (methyl methacrylate-styrene-acrylonitrile resin) resin by bulk polymerization technology, MABS high rubber powder and MSAN resin are melt blended according to the proportion to obtain MABS resin. The technical route for preparing transparent ABS resin by bulk method is relatively simple, which is to dissolve polybutadiene rubber or styrene butadiene rubber in monomers such as styrene, methyl methacrylate and acrylonitrile, and then heat to initiate polymerization. During the polymerization process, the rubber structure and size are controlled by phase inversion, and finally transparent ABS resin is prepared. At present, transparent ABS resin is widely used in household appliances, automobiles and daily necessities, and its annual consumption has reached 600,000 tons. Among them, the consumption of transparent ABS resin in the Chinese market has exceeded 300,000 tons, accounting for more than half of the global market share. In addition, with the upgrading of current MMA production technology and the release of production capacity, the price of MMA monomer will drop significantly in the future. At that time, the production cost of transparent ABS resin will drop significantly, and its market share will continue to increase.

[0004] There are many patent reports on the existing transparent ABS resin. In patent CN201480013412.7, the core-shell structure MABS toughening agent is prepared by inhibiting the infiltration of monomers such as styrene into the rubber particles, thereby realizing the preparation of MABS resin; in patent CN201611163490.2, transparent ABS resin is prepared by continuous bulk polymerization, which uses phase transition technology to control the rubber size in transparent ABS resin. However, in view of the existing technology and the currently commercially available transparent ABS resin, no in-depth research has been conducted on its anti-bending whitening performance, nor has the corresponding anti-bending whitening transparent ABS resin brand product been developed.

[0005] When transparent ABS resin is used in packaging and medical fields, the anti-blanking performance is particularly important. The main reason for the whitening is the stress whitening phenomenon caused by the resin under external stress. The cause of this stress whitening phenomenon has a clear relationship with the glass transition temperature difference between the matrix resin and the rubber phase and the actual size of the rubber particles. Reducing the glass transition temperature difference between the dispersed phase and the continuous phase and the size of the rubber phase are beneficial to improving the anti-blanking performance of transparent ABS resin. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide an anti-bending white ABS resin and a preparation method thereof. The present invention utilizes styrene and butadiene to copolymerize to increase the refractive index and glass transition temperature of the rubber phase, and then introduces acrylic monomers with low refractive index and glass transition temperature as functional monomers in the process of grafting and bulk MSAN resin preparation to adjust the refractive index and glass transition temperature, thereby achieving the suppression of stress whitening and preparing anti-bending white transparent ABS resin.

[0007] The method for preparing a fold-resistant white ABS resin of the present invention comprises the following steps:

[0008] (1) Preparation of small-particle rubber particle emulsion: 1-3 parts by weight of emulsifier and 0.1-1 parts by weight of electrolyte are added to a reactor, 150-200 parts by weight of deionized water is added, stirring is started to completely dissolve the emulsifier and electrolyte, and then 50-100 parts by weight of butadiene and 0-50 parts by weight of styrene are added; then the reactor is heated to 60-75° C., 0.2-1 parts by weight of initiator is added to initiate polymerization, the polymerization time is 8-15 hours, and after the polymerization reaction, vacuum degassing is performed to remove unreacted monomers, to obtain a small-particle rubber particle emulsion with a mass concentration of 30-60% (80-120 nm), a refractive index of 1.51-1.56, and a glass transition temperature of -100--25° C.;

[0009] (2) Take the small-particle rubber particle latex prepared in step (1) as the core layer latex, a total of 100 parts by weight on a dry basis (if the mass concentration of the small-particle rubber particles is 40%; if the dry basis is 100 parts by weight, then 250 parts by weight of the small-particle rubber particle latex is required) and add it to a graft polymerization reactor, add 1 to 3 parts by weight of an emulsifier, 0.1 to 1 part by weight of a chelating agent, and then add 0.01 to 0.1 parts by weight of a reducing agent, 0.1 to 1 parts by weight of a reducing agent, and 0.1 to 1 parts by weight of an oxidant, and heat to 50 to 75° C.; then add the graft polymerization reactor to the reaction mixture. A mixture of styrene, methyl methacrylate, acrylonitrile and acrylate is continuously added dropwise to a reaction kettle, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index so that the difference between the refractive index and the refractive index of the small-diameter rubber particles is less than 0.005, the dropping time is controlled within 2 to 5 hours, and the mass content of water in the entire reaction system is not less than 50%; after the dropping is completed, the temperature is raised to 75 to 85° C. for aging reaction for 0.5 to 2.0 hours to obtain a MABS graft copolymer latex;

[0010] (3) adding 0.5-2.5% by weight of a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85-95° C., performing solid-liquid separation after demulsification, and drying the solid product to obtain MABS high-rubber powder;

[0011] (4) 20 to 30 parts by weight of the MABS high-rubber powder obtained in step (3) are mixed with 70 to 80 parts by weight of an MSAN resin prepared by bulk polymerization (MSAN resin is obtained by bulk polymerization of monomers such as styrene, acrylonitrile, and methyl methacrylate; the preparation of MSAN resin refers to the doctoral dissertation: Xu Lu, Composition Structure Design and Performance Research of Transparent ABS Resin [D], Changchun University of Technology, 2023), and then melt-extruded, blended and granulated at 200 to 230° C. to obtain the flexural-resistant white transparent ABS resin (MABS resin); wherein the difference between the refractive index of the MSAN resin and the refractive index of the MABS high-rubber powder is less than 0.005.

[0012] The emulsifier used in step (1) and step (2) of the present invention is one or a mixture of sodium dodecyl sulfate, fatty acid potassium soap, disproportionated potassium rosin acid, and potassium oleate, and the electrolyte used in step (1) is one of sodium carbonate and potassium carbonate.

[0013] The initiator used in step (1) of the present invention is one of potassium persulfate, azobisisobutyronitrile and benzoyl peroxide.

[0014] The chelating agent used in step (2) of the present invention is sodium pyrophosphate or EDTA sodium salt, the reducing agent used is ferrous sulfate, the auxiliary reducing agent used is one of glucose, fructose, and sodium formaldehyde sulfoxylate, and the oxidant used is cumene hydroperoxide.

[0015] The acrylic acid ester in step (2) of the present invention is one of ethyl acrylate, n-butyl acrylate, isobutyl acrylate and isooctyl acrylate, preferably n-butyl acrylate or ethyl acrylate.

[0016] The flocculant used in step (3) of the present invention is magnesium sulfate or sulfuric acid, or a mixture of the two. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 : Particle size distribution diagram of the small-size rubber particle latex prepared in Example 1;

[0018] Figure 2 : Particle size distribution diagram of the large-particle rubber particle emulsion prepared in Comparative Example 2. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is described below through specific embodiments. However, it is necessary to point out that the following embodiments are only used to describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.

[0020] Example 1

[0021] (1) Preparation of small-sized rubber particles: 3 parts by mass of emulsifier potassium disproportionate rosin soap and 1 part by mass of electrolyte sodium carbonate are added to a reactor, and then 150 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 75 parts by mass of butadiene and 25 parts by mass of styrene are added. After the reactor is heated to 60°C, 0.2 parts by mass of initiator potassium persulfate are added to start polymerization. The polymerization time is 15 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers, and 179.2 parts by mass of a small-sized rubber particle emulsion is obtained, the refractive index of which is 1.534, the mass concentration of small-sized rubber particles is 58.15%, and the glass transition temperature is -49°C;

[0022] (2) Take the small-size rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight on a dry basis into a graft polymerization reactor, add 1 part by weight of potassium oleate as an emulsifier, 0.1 part by weight of sodium pyrophosphate as a chelating agent, add 0.01 part by weight of ferrous sulfate as a reducing agent and 1 part by weight of glucose as a co-reducing agent, and 0.1 part by weight of cumene hydroperoxide as an oxidant, and then heat to 50° C. Start to continuously drop a mixture of styrene, methyl methacrylate, acrylonitrile and acrylate into the reactor, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index, and the refractive index is set at 1.534, and the specific content is 20 parts by weight of styrene, 4 parts by weight of acrylonitrile, 20 parts by weight of methyl methacrylate, and 6 parts by weight of butyl acrylate. The dropping time is controlled at 2 hours, and the water content in the entire reaction system is controlled at 60%. After the dropwise addition was completed, the temperature was raised to 75° C. for aging reaction for 1 hour, thereby obtaining 224.18 parts by weight of MABS graft copolymer latex;

[0023] (3) adding 1.5% by weight of sulfuric acid as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 150 parts by weight of MABS high-rubber powder;

[0024] (4) 20 parts by weight of the MABS high-rubber powder obtained in step (3) and 80 parts by weight of MSAN resin with a refractive index of 1.534 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0025] Example 2

[0026] (1) Preparation of small-size rubber particles: 1 part by mass of emulsifier sodium dodecyl sulfate and 0.1 part by mass of electrolyte potassium carbonate are added to a reactor, and then 200 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 75 parts by mass of butadiene and 25 parts by mass of styrene are added. After the reactor is heated to 75°C, 0.2 parts by mass of initiator potassium persulfate are added to start polymerization. The polymerization time is 8 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers to obtain 301.3 parts by mass of a small-size rubber particle emulsion, the refractive index of which is 1.534, the mass concentration of small-size rubber particles is 33.62%, and the glass transition temperature is -49°C;

[0027] (2) Take the small-size rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight of dry basis into the graft polymerization reactor, add 1 part by weight of emulsifier fatty acid potassium, 0.3 part by weight of chelating agent EDTA sodium salt, 0.1 part by weight of reducing agent ferrous sulfate and 1 part by weight of auxiliary reducing agent bleaching agent, 1 part by weight of oxidizing agent cumene hydroperoxide, and heat to 50° C. Start to continuously drop a mixture of styrene, methyl methacrylate, acrylonitrile and acrylate into the reactor, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index, and the refractive index is set at 1.534, and the specific content is 20 parts by weight of styrene, 4 parts by weight of acrylonitrile, 20 parts by weight of methyl methacrylate, and 6 parts by weight of butyl acrylate. The dropping time is controlled at 2 hours, and the water content in the entire reaction system is controlled at 60%. After the dropwise addition was completed, the temperature was raised to 75° C. for aging reaction for 1 hour to obtain 350.84 parts by weight of MABS graft copolymer latex;

[0028] (3) adding 1.5% by weight of magnesium sulfate as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 150 parts by weight of MABS high-rubber powder;

[0029] (4) 20 parts by weight of the MABS high-rubber powder obtained in step (3) and 80 parts by weight of MSAN resin with a refractive index of 1.534 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0030] Example 3

[0031] (1) Preparation of small-sized rubber particles: 1 part by mass of emulsifier sodium dodecyl sulfate and 0.1 part by mass of electrolyte potassium carbonate are added to a reactor, and then 200 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 75 parts by mass of butadiene and 25 parts by mass of styrene are added. After the reactor is heated to 70°C, 0.2 parts by mass of initiator azobisisobutyronitrile is added to start polymerization. The polymerization time is 10 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers to obtain 301.3 parts by mass of a small-sized rubber particle emulsion, the refractive index of which is 1.534, the mass concentration of small-sized rubber particles is 33.62%, and the glass transition temperature is -49°C;

[0032] (2) Take the small-size rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight of dry basis into the graft polymerization reactor, add 1 part by weight of emulsifier fatty acid potassium, 0.3 part by weight of chelating agent EDTA sodium salt, add 0.05 part by weight of reducing agent ferrous sulfate and 1 part by weight of auxiliary reducing agent fructose, 0.5 part by weight of oxidizing agent cumene hydroperoxide, and heat to 55° C. Start to continuously drop a mixture of styrene, methyl methacrylate, acrylonitrile and acrylate into the reactor, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index, and the refractive index is set at 1.534, and the specific content is 20 parts by weight of styrene, 4 parts by weight of acrylonitrile, 20 parts by weight of methyl methacrylate, and 6 parts by weight of butyl acrylate. The dropping time is controlled at 2 hours, and the water content in the entire reaction system is controlled at 60%. After the dropwise addition was completed, the temperature was raised to 75° C. for aging reaction for 1 hour to obtain 350.29 parts by weight of MABS graft copolymer latex;

[0033] (3) adding 1.5% by weight of magnesium sulfate as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 150 parts by weight of MABS high-rubber powder;

[0034] (4) 20 parts by weight of the MABS high-rubber powder obtained in step (3) and 80 parts by weight of MSAN resin with a refractive index of 1.534 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0035] Example 4

[0036] (1) Preparation of small-sized rubber particles: 1 part by mass of emulsifier sodium dodecyl sulfate and 0.1 part by mass of electrolyte potassium carbonate are added to a reactor, and then 200 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 100 parts by mass of butadiene and 0 parts by mass of styrene are added. After the reactor is heated to 70°C, 0.2 parts by mass of initiator azobisisobutyronitrile is added to start polymerization. The polymerization time is 10 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers to obtain 301.3 parts by mass of a small-sized rubber particle emulsion with a refractive index of 1.515. The mass concentration of small-sized rubber particles is 33.62% and the glass transition temperature is -94.5°C.

[0037] (2) Take the small-size rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight of dry basis into the graft polymerization reactor, add 1 part by weight of emulsifier fatty acid potassium, 0.3 part by weight of chelating agent EDTA sodium salt, add 0.05 part by weight of reducing agent ferrous sulfate and 1 part by weight of auxiliary reducing agent fructose, 0.5 part by weight of oxidizing agent cumene hydroperoxide, and heat to 55° C. Start to continuously drop a mixture of styrene, methyl methacrylate, acrylonitrile and acrylate into the reactor, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index, and the refractive index is set at 1.515, and the specific content is 25 parts by weight of styrene, 10 parts by weight of acrylonitrile, 55 parts by weight of methyl methacrylate, and 10 parts by weight of butyl acrylate. The dropping time is controlled at 3 hours, and the water content in the entire reaction system is controlled at 60%. After the dropwise addition was completed, the temperature was raised to 75° C. for aging reaction for 1 hour to obtain 400.29 parts by weight of MABS graft copolymer latex;

[0038] (3) adding 1.5% by weight of magnesium sulfate as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 200 parts by weight of MABS high-rubber powder;

[0039] (4) 27 parts by weight of the MABS high-rubber powder obtained in step (3) and 73 parts by weight of MSAN resin with a refractive index of 1.515 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0040] Example 5

[0041] (1) Preparation of small-size rubber particles: 1 part by mass of emulsifier sodium dodecyl sulfate and 0.1 part by mass of electrolyte potassium carbonate are added to a reactor, and then 200 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 100 parts by mass of butadiene and 0 parts by mass of styrene are added. After the reactor is heated to 70°C, 1 part by mass of initiator benzoyl peroxide is added to start polymerization. The polymerization time is 12 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers, (i.e., 302.1 parts by mass of a small-size rubber particle emulsion is obtained, the refractive index of which is 1.515, the mass concentration of small-size rubber particles is 33.79%, and the glass transition temperature is -94.5°C;

[0042] (2) Take the small-size rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight of dry basis into the graft polymerization reactor, add 1 part by weight of emulsifier fatty acid potassium, 0.3 part by weight of chelating agent EDTA sodium salt, add 0.05 part by weight of reducing agent ferrous sulfate and 1 part by weight of auxiliary reducing agent fructose, 0.5 part by weight of oxidizing agent cumene hydroperoxide, and heat to 55° C. Start to continuously drop a mixture of styrene, methyl methacrylate, acrylonitrile and acrylate into the reactor, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index, and the refractive index is set at 1.515, and the specific content is 25 parts by weight of styrene, 10 parts by weight of acrylonitrile, 55 parts by weight of methyl methacrylate, and 10 parts by weight of ethyl acrylate. The dropping time is controlled at 3 hours, and the water content in the entire reaction system is controlled at 60%. After the dropwise addition was completed, the temperature was raised to 75° C. for aging reaction for 1 hour to obtain 398.79 parts by weight of MABS graft copolymer latex;

[0043] (3) adding 1.5% by weight of magnesium sulfate as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 200 parts by weight of MABS high-rubber powder;

[0044] (4) 27 parts by weight of the MABS high-rubber powder obtained in step (3) and 73 parts by weight of MSAN resin with a refractive index of 1.515 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0045] Comparative Example 1

[0046] (1) Preparation of small-sized rubber particles: 3 parts by mass of emulsifier potassium disproportionate rosin soap and 1 part by mass of electrolyte sodium carbonate are added to a reactor, and then 150 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 75 parts by mass of butadiene and 25 parts by mass of styrene are added. After the reactor is heated to 60°C, 0.2 parts by mass of initiator potassium persulfate are added to start polymerization. The polymerization time is 15 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers to obtain 254.2 parts by mass of a small-sized rubber particle emulsion with a refractive index of 1.534. The mass concentration of small-sized rubber particles is 40.99% and the glass transition temperature is -49°C.

[0047] (2) Take the small-size rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight on dry basis into the graft polymerization reactor, add 1 part by weight of emulsifier potassium oleate, 0.1 part by weight of chelating agent sodium pyrophosphate, 0.01 part by weight of reducing agent ferrous sulfate and 1 part by weight of auxiliary reducing agent glucose, 0.1 part by weight of oxidizing agent isopropylbenzene hydroperoxide, and then heat to 50°C. Start to continuously add a mixture of styrene, methyl methacrylate and acrylonitrile, totaling 50 parts by weight, to the reactor, wherein the ratio of styrene, methyl methacrylate and acrylonitrile is calculated according to the refractive index, and the refractive index is set at 1.534, and the specific content is 20 parts by weight of styrene, 4 parts by weight of acrylonitrile, and 26 parts by weight of methyl methacrylate. The dropping time is controlled at 2 hours, and the water content in the entire reaction system is controlled at 60%. After the dropping is completed, the temperature is raised to 75°C for aging reaction for 1 hour to obtain 296.17 parts by weight of MABS graft copolymer latex;

[0048] (3) adding 1.5% by weight of sulfuric acid as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 150 parts by weight of MABS high-rubber powder;

[0049] (4) 20 parts by weight of the MABS high-rubber powder obtained in step (3) and 80 parts by weight of MSAN resin with a refractive index of 1.534 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0050] Comparative Example 2

[0051] (1) Preparation of large-size rubber particles: 3 parts by mass of emulsifier potassium disproportionate rosin soap and 1 part by mass of electrolyte sodium carbonate are added to a reactor, and then 50 parts by mass of deionized water are added. After stirring to completely dissolve the emulsifier and electrolyte, 75 parts by mass of butadiene and 25 parts by mass of styrene are added. After the reactor is heated to 60°C, 0.2 parts by mass of initiator potassium persulfate are added to start polymerization. The polymerization time is 15 hours. After the polymerization reaction, vacuum degassing is performed to remove unreacted monomers, and 154.2 parts by mass of large-size rubber particle emulsion (particle size range is about 300nm) can be obtained. The refractive index is 1.534, the mass concentration of large-size rubber particles is 67.57%, and the glass transition temperature is -49°C;

[0052] (2) Take the large-diameter rubber particle latex prepared in step (1) as the core layer latex, add a total of 100 parts by weight on a dry basis into a graft polymerization reactor, add 1 part by weight of potassium oleate as an emulsifier, 0.1 part by weight of sodium pyrophosphate as a chelating agent, add 0.01 part by weight of ferrous sulfate as a reducing agent and 1 part by weight of glucose as a co-reducing agent, and 0.1 part by weight of cumene hydroperoxide as an oxidant, and then heat to 50° C. Start to continuously drop a mixture of styrene, methyl methacrylate, acrylonitrile and acrylate into the reactor, wherein the proportion of styrene, methyl methacrylate, acrylonitrile and acrylate is calculated according to the refractive index, and the refractive index is set at 1.534, and the specific content is 20 parts by weight of styrene, 4 parts by weight of acrylonitrile, 20 parts by weight of methyl methacrylate, and 6 parts by weight of butyl acrylate. The dropping time is controlled at 2 hours, and the water content in the entire reaction system is controlled at 60%. After the dropwise addition was completed, the temperature was raised to 75° C. for aging reaction for 1 hour to obtain 200.2 parts by weight of MABS graft copolymer latex;

[0053] (3) adding 1.5% by weight of sulfuric acid as a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85° C., performing solid-liquid separation by suction filtration after demulsification, and drying the solid product to obtain 150 parts by weight of MABS high-rubber powder;

[0054] (4) 20 parts by weight of the MABS high-rubber powder obtained in step (3) and 80 parts by weight of MSAN resin with a refractive index of 1.534 prepared by bulk polymerization are melt-extruded, blended and granulated at 200° C. to obtain 100 parts by weight of flexural-resistant white transparent ABS resin (MABS resin).

[0055] The transparent ABS resin obtained in the above examples and comparative examples was prepared into standard notched impact specimens and tensile specimens according to ASTM D256 and ASTM D638 standards and tested. The transparent ABS resin was prepared into standard impact, tensile and light transmission specimens based on ASTM D256 (2010) and ASTM D 638 (2014) and ISO 13468-2 (1999) for testing.

[0056] The anti-whitening performance test is to prepare the transparent ABS resin in the embodiment and the comparative example into a standard size sample of 3mm*100mm*100mm, use a steel ball with a mass of 500g and a diameter of 50mm to vertically drop from a height of 300mm to hit the transparent ABS resin sample, and then record the stress whitening diameter, and take the average result of 10 times as the actual value. The specific test results are shown in Table 1:

[0057] Table 1: Performance data of products of examples and comparative examples

[0058]

[0059] It can be seen from the examples that the impact strength of the prepared transparent ABS resin is greater than 100 J / m, the transmittance is greater than 88%, the haze is less than 6, which meets the requirements of daily use, and the diameter of the stress whitening area is less than 3 mm, which has obvious anti-whitening performance (reducing stress whitening caused by external force on the material). The difference between Example 1 and Comparative Example 1 lies in the use of acrylate monomers. Example 1 uses acrylate monomers in the graft polymerization stage, while Comparative Example 1 does not use them, which shows that the introduction of acrylate monomers will improve the anti-whitening performance of the transparent ABS resin. The difference between Example 1 and Comparative Example 2 is that the particle size of the rubber particle emulsion prepared in step (1) is different. The particle size distribution of the two is as follows: Figure 1 and Figure 2 As shown, the rubber particles prepared in step (1) of Examples 1 to 5 have a particle size of about 100 nm, which is a small-particle latex. The rubber particles prepared in step (1) of Comparative Example 2 are large-particle latex with a particle size of about 300 nm. It can be concluded that the anti-whitening performance of the transparent ABS resin prepared from small-particle rubber particles is better than that of similar products with large particles.

Claims

1. A method for preparing fold-resistant white ABS resin, comprising the following steps: (1) Preparation of small-size rubber particle emulsion: 1-3 parts by weight of emulsifier and 0.1-1 parts by weight of electrolyte are added to a reaction kettle, 150-200 parts by weight of deionized water are added, stirring is started to completely dissolve the emulsifier and electrolyte, and then 50-100 parts by weight of butadiene and 0-50 parts by weight of styrene are added; then the temperature of the reaction kettle is raised to 60-75° C., 0.2-1 parts by weight of initiator are added to initiate polymerization, the polymerization time is 8-15 hours, and after the polymerization reaction, vacuum degassing is performed to remove unreacted monomers, thereby obtaining a small-size rubber particle emulsion with a mass concentration of 30-60%; (2) taking the small-size rubber particle latex prepared in step (1) as the core layer latex, adding a total of 100 parts by weight on a dry basis into a graft polymerization reaction kettle, adding 1 to 3 parts by weight of an emulsifier, 0.1 to 1 part by weight of a chelating agent, and then adding 0.01 to 0.1 parts by weight of a reducing agent, 0.1 to 1 parts by weight of a reducing agent, and 0.1 to 1 parts by weight of an oxidizing agent, and heating the reaction kettle to 50 to 75° C.; then continuously dropping a mixture of styrene, methyl methacrylate, acrylonitrile and acrylic acid ester, totaling 50 to 100 parts by weight, into the graft polymerization reaction kettle, wherein the proportions of styrene, methyl methacrylate, acrylonitrile and acrylic acid ester are calculated according to the refractive index so that the difference between the refractive index and the refractive index of the small-size rubber particles is less than 0.005, the dropping time is controlled within 2 to 5 hours, and the mass content of water in the entire reaction system is not less than 50%; after the dropping is completed, the temperature is raised to 75 to 85° C. for aging reaction for 0.5 to 2.0 hours to obtain a MABS graft copolymer latex; (3) adding 0.5-2.5% by weight of a flocculant to the MABS graft copolymer latex obtained in step (2), flocculating and demulsifying at 85-95° C., performing solid-liquid separation after demulsification, and drying the solid product to obtain MABS high-rubber powder; (4) Mixing 20 to 30 parts by weight of the MABS high-rubber powder obtained in step (3) with 70 to 80 parts by weight of MSAN resin, and then performing melt extrusion, blending and granulation at 200 to 230° C. to obtain the anti-bending white transparent ABS resin; wherein: The difference between the refractive index of MSAN resin and that of MABS high-rubber powder is less than 0.

005.

2. The method for preparing a flexural-resistant white ABS resin according to claim 1, characterized in that: In step (1), the particle size of the small-size rubber particles is 80 to 120 nm, the refractive index is 1.48 to 1.56, and the glass transition temperature is -100 to -25°C.

3. The method for preparing a flexural-resistant white ABS resin according to claim 1, characterized in that: The emulsifier used in step (1) and step (2) is one or a mixture of sodium dodecyl sulfate, fatty acid potassium soap, potassium disproportionate rosin acid, potassium oleate, and the electrolyte used in step (1) is one of sodium carbonate or potassium carbonate.

4. The method for preparing a flexural-resistant white ABS resin according to claim 1, characterized in that: The initiator used in step (1) is one of potassium persulfate, azobisisobutyronitrile and benzoyl peroxide.

5. The method for preparing a flexural-resistant white ABS resin according to claim 1, characterized in that: The chelating agent used in step (2) is sodium pyrophosphate or EDTA sodium salt, the reducing agent used is ferrous sulfate, the co-reducing agent used is one of glucose, fructose, and sodium formaldehyde sulfoxylate, and the oxidizing agent used is cumene hydroperoxide.

6. The method for preparing a flexural-resistant white ABS resin according to claim 1, characterized in that: The acrylic acid ester in step (2) is one of ethyl acrylate, n-butyl acrylate, isobutyl acrylate and isooctyl acrylate.

7. The method for preparing a flexural-resistant white ABS resin according to claim 1, characterized in that: The flocculant used in step (3) is magnesium sulfate or sulfuric acid, or a mixture of the two.

8. A flexural-resistant white ABS resin, characterized in that: The method is prepared by any one of claims 1 to 7.

Citation Information

Patent Citations

  • Transparent ABS resin and transparent ABS resin composition

    CN105008406B

  • A method for preparing transparent ABS resin using a continuous bulk apparatus

    CN106699981B

  • Transparent ABS resin composition having superior shock resistance, scratch resistance, and transparency

    CN104136530A

  • Styrene-based thermoplastic resin composition, production method of styrene-based thermoplastic resin composition, molded article, and production method of molded article

    CN113574111A

  • Method for preparing transparent ABS (Acrylonitrile Butadiene Styrene) resin based on pressure agglomeration technology

    CN114736334A

Cited By

  • Antistatic transparent ABS (Acrylonitrile Butadiene Styrene) resin and preparation method thereof

    CN121086436A